The Role of the Communication and Informatics Service in Preventing the Spread of False Information to the Public in Sidoarjo District - Safira Tasya Nanda Sari; Tukiman Tukiman (Universitas Medan Area, 2022)
In the current era of digitalization, everyone can easily create and share information without ascertaining whether the information is valid or invalid. In Sidoarjo District, Government agencies that play a role in preventing the spread of false information continue to occur in the public is a role that should be carried out by the communications and information service. The writing of this study aims to find out and analyze how the role played by the Communication and Information service of Sidoarjo District in preventing the spread of false information to the public in Sidoarjo District based on the focus of this research, namely the duties and functions of the Sidoajo District Communication and Information Service, especially in the Information and Communication Public Management Sector. The data are presented through direct observation and interviews qualitatively analyzed. This study concludes that until now there is no policy or Standart Operating Procedure (SOP) that regulates the prevention of the spread of false information to the people of Sidoarjo, the action taken In handling cases of false information is only to clarify based on reports received from the people of Sidoarjo District.